Quality of life among menopausal women in an urban area of Siliguri, West Bengal, India - Adhikari, Banalata; Biswas, Romy (International Journal Of Community Medicine And Public Health, 2019)
Background: Women who lay the foundation of the whole society are most neglected in our society, especially in their mid-life. Physical and psychosocial symptoms among post -menopausal women had a positive relation with the quality of life. Methods: A total of 110 women of an urban area of North Bengal region of West Bengal, India were interviewed with help of schedule to obtain information regarding the personal characteristics and MENQOL tool to assess four domains means on the basis of 29 symptoms. Results: The mean menopausal age was 44.58±3.11 years. The means and standard deviation found in different domains are, vasomotor domain (5.35±2.94), physical domain (27.95±10.25), psychosocial domain (13.81±4.70) and sexual domain (1.99±2.91). In the vasomotor domain, muscles ache, joint ache and low back ache were the common symptoms. In psycho-social domain, 99% of the women suffered from poor memory and 97.2% of them felt depressed or down/blue. In sexual domain, 33.6% were bothered by changes in their sexual desires and avoided intimacy. In physical domain, age category, financial and decision autonomy had significant association. In the sexual domain, age category, literacy status, money and sexuality had a significant difference. Conclusions: Post-menopausal women are vulnerable group for whom appropriate and practical measures should be provided in their post-menopausal age in order to have a contented and pleasant life till they die.